Molecular evolutionary relationships of Euphorbia scordifolia Jacq. within the genus inferred from analysis of internal transcribed spacer sequences (Bangladesh Journal of Plant Taxonomy, 2015)
The present study explored molecular phylogenetic analysis of 28 species of Euphorbia L. for the identification and establishment of molecular evolutionary relationships of Euphorbia scordifolia Jacq. within the genus based on the internal transcribed spacers (ITS) sequences (ITS1-5.8S-ITS2) of nuclear ribosomal DNA (nrDNA). The sequence similarity search using Basic Local Alignment Search Tool (BLAST) of the ITS sequence of E. scordifolia showed the closest sequence similarity to E. supina Raf. The analysis of ITS sequence data revealed four major clades consistent with subgeneric classifications of the genus. Molecular data support placement of E. scordifolia in the subgenus Chamaesyce.Bangladesh J. Plant Taxon. 22(2): 111-118, 2015 (December)